Evolution of Placental Hormones: Implications for Animal Models - Carter, Anthony M. (Frontiers in Endocrinology, 2022)
Human placenta secretes a variety of hormones, some of them in large amounts. Their effects on maternal physiology, including the immune system, are poorly understood. Not one of the protein hormones specific to human placenta occurs outside primates. Instead, laboratory and domesticated species have their own sets of placental hormones. There are nonetheless several examples of convergent evolution. Thus, horse and human have chorionic gonadotrophins with similar functions whilst pregnancy-specific glycoproteins have evolved in primates, rodents, horses, and some bats, perhaps to support invasive placentation. Placental lactogens occur in rodents as well as primates though evolved through duplication of different genes and with functions that only partially overlap. There are also placental hormones, such as the pregnancy-associated glycoproteins of ruminants, that have no equivalent in human gestation. This review focusses on the evolution of placental hormones involved in recognition and maintenance pregnancy, in maternal adaptations to pregnancy and lactation, and in facilitating immune tolerance of the fetal semiallograft. The contention is that knowledge gained from laboratory and domesticated mammals can translate to a better understanding of human placental endocrinology, but only if viewed in an evolutionary context.